Mixed comparison of different exercise interventions on physical functioning in adult patients with morbid obesity following bariatric surgery: a systematic review and network meta-analysis - Hu, Chen; Sun, Dong; Fang, Yufei; Cen, Xuanzhen; Xu, Yining; Baker, Julien S.; Gu, Yaodong (Frontiers in Endocrinology, 2024)
Introduction: People who are overweight following bariatric surgery (BS) often need physical exercise to help with body function. However, it is not known which exercise interventions are more effective in improving physical function. Methods: PubMed, Web of Science, Embase, and Cochrane Library databases were systematically searched for randomized controlled trials evaluating the effects of different exercise interventions on physical function in patients with excessive obesity following bariatric surgery. Outcome measures included effect sizes for physical function (PF), expressed as the number of stand-sit passes or the maximum distance walked within a time limit, body mass index (BMI), and blood pressure (BP). A systematic review was conducted to screen and synthesize the included studies, followed by a network meta-analysis for quantitative data analysis. Results: A total of 15 studies involving 1011 patients were included. For PF, telehealth core exercise had the highest probability (0.46) of being the most effective intervention. For BMI, nutritional behavior and guided exercise, intervention had the highest probability (0.27) of being the most effective. Regarding BP, exercise prescription had the highest probability (0.47) for improving systolic blood pressure, while aerobic and strength and flexibility training had the highest probability (0.6) for improving diastolic blood pressure. Discussion: Telehealth core exercise may be the most effective intervention for enhancing PF in overweight patients after bariatric surgery. Changes in BMI and BP with different postoperative exercise interventions may depend more on the surgery itself than the exercise modality. More specifically designed RCTs are needed for reliable conclusions.